2020
DOI: 10.1186/s12877-020-01555-2
|View full text |Cite
|
Sign up to set email alerts
|

Nurse-patient interaction and self-transcendence: assets for a meaningful life in nursing home residents?

Abstract: Background: Due to the shift to an older population worldwide and an increased need for 24-h care, finding new and alternative approaches to increase wellbeing among nursing home (NH) residents is highly warranted. To guide clinical practice in boosting wellbeing among NH residents, knowledge about nurse-patient interaction (NPI), inter-(ST1) and intra-personal (ST2) self-transcendence and meaning-in-life (PIL) seems vital. This study tests six hypotheses of the relationships between NPI, ST1, ST2 and PIL amon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 116 publications
(152 reference statements)
2
19
0
1
Order By: Relevance
“…© Gørill Haugan sense of coherence, and alleviation of loneliness, anxiety and depression. What is more, positively perceived nurse-patient interaction strengthens residents' joy-of-life [105], meaningin-life, and self-transcendence [55,97]; the latter two have shown significant impact on physical, emotional, social, functional, and spiritual wellbeing [21,57,119,[130][131][132][133][134]. Thus, the interaction between the nurse and the older adult can be used to promote health and well-being.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…© Gørill Haugan sense of coherence, and alleviation of loneliness, anxiety and depression. What is more, positively perceived nurse-patient interaction strengthens residents' joy-of-life [105], meaningin-life, and self-transcendence [55,97]; the latter two have shown significant impact on physical, emotional, social, functional, and spiritual wellbeing [21,57,119,[130][131][132][133][134]. Thus, the interaction between the nurse and the older adult can be used to promote health and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Due to sample size, all paths were not tested in one complex SEM model. Thus, different SEM models of the hypothesized relations between the latent constructs of nurse-patient interaction and (1) self-transcendence (interpersonal and intrapersonal) [97], (2) meaning-in-life [55,119], (3) hope [120], (4) anxiety and depression [45], and (5) joy-of-life [105], were tested by means of LISREL 8.8 [121] and Stata 15.1 [122], while the assoications with sense of coherenec and loneliness were tested by regression analyses using IBM SPSS Statistics [123].…”
Section: Analysesmentioning
confidence: 99%
“…For example, Reed [11] identified four patterns of self-transcendence to be more predominant in nondepressed than depressed oldest-old adults. Similarly, results from several studies by Haugan and colleagues support interpersonal and intrapersonal self-transcendence as clinically important in nurse-patient interactions to promote mental health in older adult nursing home residents [37,38,50,51] and physical, emotional, social, functional, and spiritual wellbeing of older adults in nursing homes [24,25,35,39]. Intrapersonal self-transcendence was among particularly significant health-promoting factors in long-term care residents [36].…”
Section: Later Adulthoodmentioning
confidence: 81%
“…Selftranscendence is a vital but not inexhaustible psychosocial resource in older adults. For example, two different Norwegian studies among older adults in nursing homes showed that both interpersonal and intrapersonal selftranscendence were significantly influenced by the residents' perceived nurse-patient interaction [37,51]. Walton and colleagues [53] identified a significant inverse relationship between self-transcendence and loneliness in older adults; this was supported by a recent Norwegian study among nursing home residents [54].…”
Section: Later Adulthoodmentioning
confidence: 88%
See 1 more Smart Citation